Occupational Exposure to Pesticides Among Farmworkers in Morocco: A Study Framework for Endocrine and Epigenetic Effect Assessment - Kaoutar Chbihi; Aziza Menouni; Imane Berni; Hala Chetouani; Said Abou-Said; Amal Amellah; Robin Lebegge; Eline Verscheure; Jeroen Vanoirbeek; Radu-Corneliu Duca; Lode Godderis; Samir El Jaafari (Toxics)
Pesticides are compounds of major use in agriculture worldwide. Nevertheless, many pesticide chemicals are classified as endocrine disruptors and potentially carcinogens. Farmers and farmworkers are particularly exposed and are at high risk of developing health-related impairments. In Morocco, the lack of awareness towards pesticide hazards and the inappropriate application of safety measures might increase the exposure as well as the risks of health concerns. In this paper, we present the framework of a study designed to assess pesticide exposure among Moroccan farmers and farmworkers and to evaluate potential health effects, namely endocrine and epigenetic impacts. Human biological monitoring will be conducted to determine pesticide levels in urine following the development and validation of sensitive chromatography methods (SPE, UPLC-MS/MS). Biomarkers of exposure include a set of parent and metabolite pesticide compounds (organophosphates, pyrethroids, triazines and urea-based pesticides). Thyroid and reproductive hormones (TSH, T3, T4, FSH and LH) as well as global and specific DNA methylation markers (5-mC, 5-hmC, N6-mA, THRB and LHR) are selected as biomarkers of effects. This provides guiding steps and methods to perform reliable exposure evaluation and health impact assessment. This study aims to expand the current knowledge on the endocrine and epigenetic risks related to pesticides, especially in low- and middle-income countries.